Surface-modified mucoadhesive microparticles as a controlled release system for oral delivery of insulin - Mumuni, Momoh A. (Heliyon, 2019)
To overcome barriers and improve oral bioavailability of insulin delivery has been a mirage to formulation scientists due to instability of the insulin after oral administration. Microparticle (MP) composed of chitosan and snail mucin was prepared via double emulsion method for oral delivery of insulin. Microparticles were characterized by differential scanning calorimetry, Fourier transform infrared spectroscopy and scanning electron microscopy. The encapsulation efficiency (EE) of the insulin-loaded MPs were evaluated. Insulin release behavior was evaluated in acidic and phosphate buffer (pH 1.2 and 7.4) at 37 °C. Bioactivities of insulin-loaded MPs were evaluated in a diabetic animal model after oral administration. The insulin-loaded MPs showed irregular shape with a zeta potential (>29 mV). The encapsulation efficiency and drug loading were >75 and 28 %, respectively. The in vitro release shows >80 % release of insulin over 12 h in a sustained manner. The insulin-MPs significantly reduced blood glucose levels (>50 %) compared to positive control and the effect lasted for over 8 h. This study suggests that insulin-MPs as prepared would be potential carriers for oral delivery of insulin.